Talcott Parsons and the keynesian economists. On the concepts of individual agent, organizations and institutions - Hernández-Chuliá, Sagar (Sociedad y Economía, 2020)
In this research, it is intended to apply the comparative method to theoretical contributions that the keynesian economists and Talcott Parsons carry out around the concepts of individual agents, organizations and institutions. In view of the results, it is concluded that while Parsons shares the characterization of the individual agents carried out by both Keynes and the Post-Keynesian authors, he also uses formal models, as do the New Keynesians. In addition, in the inter-organizational area, it legitimizes the role that the State can play in the economy, highlighting as post-Keynesians, the positive role that unions can develop. Finally, Parsons also agrees with post-Keynesian economists, particularly with Kaldor, because of the way in which he understands institutions as general and natural phenomena that can present a low profile of conflict.